Complete right ventricular obstruction caused by a giant cardiac myxoid sarcoma. (June 2014) - Soo, Alan; Molloy, Fiona; Herron, Brian; Parissis, Haralabos
Myxoid sarcoma is a very rare variant of primary malignant sarcoma of the heart, which presents like a myxoma. We describe the case of 21-year-old man with a giant myxoid sarcoma occupying most of the right ventricle. He underwent emergency surgery to resect the tumor and replace the tricuspid valve which was infiltrated. Chemotherapy and radiotherapy were given postoperatively.